A BIBLIOMETRIC ANALYSIS OF READING STRATEGY (DATABASES SCOPUS AND GOOGLE SCHOLAR 2016-2021) - Hijril Ismail (UICELL, 2021)
Reading strategy is an essential skill required by the students to gain knowledge and information about certain reading texts. The purpose of this study is to provide an extensive literature review on reading strategy. Articles were located through publish or perish software, Google Scholar, and Scopus. We analyzed 92 articles from 2016 to 2021. Mendeley software was applied to manage and resume the references. The researchers reviewed this database and attempted to classify articles using VOSviewer software. Eight clusters have reviewed the words most frequently occurring in each group were achievement, examination, attitude, comprehension, evidence, case, contribution, and case study. This cluster represents the research streams of reading strategy. Keywords: reading strategy, bibliometric analysis, publish or perish software, Scopus, and VOSviewer